Data for: Separating triplet exciton diffusion from triplet-triplet annihilation by the introduction of a mediator - Börjesson, Karl (University of Gothenburg, 2024)
The raw data and the scripts used to perform simulations for the article "Separating triplet exciton diffusion from triplet-triplet annihilation by the introduction of a mediator" by Andrew J. Carrod, Anton M. Berghuis, Andrew Monkman, Andrew Danos, and Karl Börjesson are here stored.

The data consist of:

Raw and processed absorption and emission spectra for various rubrene, tetracene, and porphyrin films.
Dynamic and static emission quenching of a porphyrin by tetrancene in solution and film.
Upconversion spectra and integrated upconversion as a function of excitation intensity.
Monte Carlo simulations
Scripts used for the Monte Carlo simulations

The first part of the filename indicate to which figure in the article that the data belongs to. The file ending describes what type of data that the file consist of:

".txt" tab delimited raw data file.
".svg" figure file, originally compiled using the Inkscape software.
".opju" figure file, made using the data in the corresponding ".txt" file, can be opened using he Origin software.
".zip" compressed (by 7-zip) output files from simulations. The script used for simulations is named "Sim_Script_Matlab.zip" and needs the sofware MatLab to run.

The simulation script consists of:

A main script "main_TTA_diffusion", from where the script is runed
A file where all input data is defined "SimulationVariables"
Parameters can be swept using the "MakeSweepFilesJSON" file
Several functions that should not be changed

The simulation script generates an output folder containing all output data together with the variables used in the input data file.

Rådata och skript som användes för att utföra simuleringar för artikeln "Separating triplet exciton diffusion from triplet-triplet annihilation by the introduction of a mediator" av Andrew J. Carrod, Anton M. Berghuis, Andrew Monkman, Andrew Danos och Karl Börjesson finns här lagrade.

Data innehåller:

Rå- och bearbetade absorptions- och emissionsspektra för olika rubren-, tetracen- och porfyrinfilmer.
Dynamisk och statisk emissionssläckning av porfyrin med tetracen i lösning och film.
Uppkonverteringsspektra och integrerad uppkonvertering som en funktion av exciteringsintensitet.
Monte Carlo-simuleringar.
Skript som används för Monte Carlo-simuleringarna.

Den första delen av filnamnet anger vilken figur i artikeln som data tillhör. Filändelsen beskriver vilken typ av data som filen består av:

".txt" tabbavgränsad rådatafil.
".svg" figurfil, ursprungligen kompilerad med programvaran Inkscape.
".opju"-figurfilen, gjord med hjälp av data i motsvarande ".txt"-fil, kan öppnas med Origin-programvaran.
".zip" komprimerade (med 7-zip) utdatafiler från simuleringar. Skriptet som används för simuleringar heter "Sim_Script_Matlab.zip" och behöver programvaran MatLab för att köras.

Simuleringsskriptet består av:

Ett huvudskript, "main_TTA_diffusion", från vilket simuleringen körs.
En fil där alla indata definieras, "SimulationVariables".
Möjlighet att svepa parametrar med hjälp av filen "MakeSweepFilesJSON".
Flera funktioner som inte bör ändras.

Simuleringsskriptet genererar en utdata-mapp som innehåller all utdata tillsammans med de variabler som användes i indatafilen.
Data for: Separating triplet exciton diffusion from triplet-triplet annihilation by the introduction of a mediator
Keywords: spectroscopy; spektroskopi; energy transfer; energiöverföring; photochemistry; fotokemi; physical chemistry; fysikalisk kemi; triplet triplet annihilation; triplet triplet annihilation; Natural Sciences; Naturvetenskap; Chemical Sciences; Kemi; Physical Chemistry; Fysikalisk kemi